The Potency of Anting Anting (Acalypha indica L.) Leaf Extract as An Acaricide on Boophilus microplus in Larvae and Adult Stages In Vitro - Fitri Nurdiana; Rahmi Sugihartuti; Bambang Sektiari Lukiswanto (Journal of Parasite Science (JoPS), 2021)
The purpose of this study was to determine the potency of anting-anting leaf extract (Acalypha indica L.) as an acaricide against larval and adult Boophilus microplus in vitro by observing the mortality rate of B. microplus. The present study design was a completely randomized design. This study used five treatments, including: Tween 80 1% and aquadest (K-), Neguvon (K+), anting-anting leaf extract with a concentration of 3.125% (P1), 6.25% (P2), and 12.5% (P3 ). Each treatment used 5 repetitions and each repetition used 6 B. microplus larval stages and 5 B. microplus adults. Observations were made for 5 hours for the larval stage of B. microplus and 24 hours for the adult stage of B. microplus. Boophilus microplus is declared dead if there is no movement at all when touched with a needle. The data obtained were analyzed using factorial ANOVA and continued with Duncan's multiple distance test. The results showed that the 12.5% anting anting leaf extract treatment showed no significant difference with the treatment using Neguvon. (p>0.05) in larval stage B. microplus, but in adult B. microplus showed a significant difference with Neguvon (p<0.05). The results of the statistical test can be concluded that the extract of anting-anting leaf (A. indica L.) has the potential as an acaricide of B. microplus larval stage in vitro. The higher the concentration of anting anting leaf extract, the higher the acaricide activity.